2021
DOI: 10.1002/jdd.12566
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and usability study of a pilot immersive virtual reality‐based empathy training for dental providers

Abstract: Social determinants of health (SDOH) significantly impact individuals' engagement with the healthcare system. To address SDOH-related oral health disparities, providers must be equipped with knowledge, skills, and attitudes (KSAs) to understand how SDOH affect patients and how to mitigate these effects. Traditional dental school curricula provide limited training on recognizing SDOH or developing empathy for those with SDOH-related access barriers. This study describes the design and evaluation of such a virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
(13 reference statements)
2
25
0
Order By: Relevance
“…Similar findings have been reported among medical students: those participating in fully immersive VR reported significantly higher gains in knowledge than students in partially immersive VR [ 33 ]. Another recent study focused on social determinants of health and empathy in dental education found that 360-degree, immersive VR improved cognitive, affective, and skills-based learning in residents and faculty [ 34 ]. Overall, these findings combined with the qualitative responses from our participants underscore the importance of immersive VR to enhance the user experience and improve learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported among medical students: those participating in fully immersive VR reported significantly higher gains in knowledge than students in partially immersive VR [ 33 ]. Another recent study focused on social determinants of health and empathy in dental education found that 360-degree, immersive VR improved cognitive, affective, and skills-based learning in residents and faculty [ 34 ]. Overall, these findings combined with the qualitative responses from our participants underscore the importance of immersive VR to enhance the user experience and improve learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies applied virtual strategies in teaching miscellaneous dental skills; critical thinking, 82 professionalism, 83 scientific writing, 84 knowledge of home dental practice, 85 head and neck anatomy, 86 dental morphology, 87 dental diagnosis, 88 and social aspects of dental care delivery. 89 Total included participants were n = 543. Characteristics of the selected studies are shown in ►Table 9.…”
Section: Miscellaneous Dental Skillsmentioning
confidence: 99%
“…Within these formats, communication skills, reporting skills in radiographic interpretation of bony lesions, intraoral anesthetic administration, cavity or crown preparation, or polymerization skills for fillings are practiced on patient cases. 1,2,5,[7][8][9][10][11]14,[17][18][19][20] Communication and patient case assessments in the dental field 21,22 or surgical skills with related clinical anatomy with lecturers, 23 classical anatomy teaching 24,25 or surgical training for orthognathic surgery in the sense of Le Fort I surgery and implantological procedures 6,12 can also be trained in XR in the meantime.…”
Section: Introductionmentioning
confidence: 99%